Literary Creation and Reception as a Multisensorial Cerebral Experience - Miguel-Pueyo, Carlos (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
From the very moment of poetic inspiration until the moment of reception, the limits of literature remain in the context of human brain. Since the first literary manifestations in History, writers ana artists have sensed and explored the footprints of creativity, as well as the similar sensorial experiences that the human being experiments while perceiving the different artistic products, especially, literature, painting, and music. Romanticism was the historical moment when Fine Arts blurred their limits, responding to the linguistic insufficiency with a work of total art, Gesamtkunstwerk, in which the arts share their tools, with other sister arts. In the 20th and 21st-centuries, efforts in the field of Neuroscience and Neuro Aesthetics, have striven to prove how the human brain works in the process of human perception of multisensorial experiences, through the stimuli pertaining to literature, painting, and music. This paper proposes a Neuro aesthetic analysis of simultaneous perception of audio and visual stimuli, in others words, musical and pictorial stimuli, while reading the narrative text, taking into account recent studies in Neuroscience.
Keywords: brain; paint; music; literature; creation